Notes on the Dianous aereus complex with description of a new species (Coleoptera, Staphylinidae) - Tang, Liang; Hu, Cheng-Zhi (Zootaxa, 2018)
Dianous pseudaerator Tang and Hu, sp. n., a new species of the Dianous aereus complex from China, is described and illustrated. Male of D. brevicornis Puthz, 2000, is discovered for the first time. New distributional records are reported for D. vietnamensis Puthz, 1980, D. rougemontianus Puthz, 2000, and D. aerator Puthz, 2016.